A novel homozygous nonsense mutation (p.Y78*) in TMPRSS6 gene causing iron-refractory iron deficiency anemia (IRIDA) in two siblings - Çakmaklı, Seda; Kaplan, Çiğdem; Uzunoğlu, Mehmet; Büyükbayram, Merve; Görgülü, Emel; Zarif, Nurten Özkan; Keskin, Ebru Yılmaz (The Turkish Journal of Pediatrics, 2020)
Iron-refractory iron deficiency anemia (IRIDA) is an inherited iron metabolism disorder caused by mutations in TMPRSS6 gene encoding matriptase-2, which results in increased hepcidin synthesis. The hallmarks of the disease are hypochromic microcytic anemia, low transferrin saturation, slightly low or normal ferritin levels in contrast to classic iron deficiency anemia (IDA), inadequate response to oral iron, and only a partial response to parenteral iron. We report here a 6-year-old Syrian boy with unexplained microcytic anemia since one year of age. Genetic analysis of the TMPRSS6 gene revealed a novel homozygous nonsense mutation in exon 3 (c.234C > G; p.Y78* or p.Tyr78*). In the presence of hypochromic microcytic anemia accompanied by atypical iron parameters not in accordance with classic IDA, and inadequate response to iron therapy, IRIDA should be remembered in the differential diagnosis.